Tourism development: an analysis of the role of local government and its capacity - Liew Heng Mel @ Janie Uew; Kamarul Mizal Mazuki; Tini Maizura Mokhtar; Kamisan Pusiran (Universiti Malaysia Sabah, 2006)
Tourism is a rapidly growing trend and has become one of the largest industries in the world. Tourist arrivals into Malaysia rose by 4.3% to 12,213,767 in the first 9 months of 2007 compared with 11,711,440 in the same period the previous year with an average of 1.3 million foreign visitors a month (Ministry of Tourism, 2008). The figures up to December 2007 for tourism to Malaysia have not been finalized for release by the government, but the "Tourism Malaysia" group is confident of surpassing 2006's 15.7 million tourist arrivals and RM26.6 billion in terms of tourist receipts. Tourism Malaysia is targeting 20 million visitors and RM38 billion in tourist receipts by the end of the Visit Malaysia Year 2007 campaign. In Sabah, it is the second largest contributor to the state's GOP (Ministry of Tourism, 2008), with arrivals totalling 2.4 million in 2007 (MASB, 2008) and a growth of 18.5%. Tourist destinations worldwide are fadng a growing number of challenges in developing, managing and marketing their products in an increasingly competitive and rapidly-changing environment, including Sabah. Not only do destinations need to appeal to new audiences, but they also find that they need to constantly reinvent themselves to ensure repeat visitation. A growing range o destination types are being marketed in Sabah which bring new perspectives and challenges not only affecting the urban areas (like Kota Kinabalu, Sandakan, Tawau) but also rural areas such as Ranau, Kudat, Beaufort, Sipitang, Tenom, Tambunan and Keningau. The very complexity of tourism makes its administration difficult. Although tourism in Sabah comes within the area of responsibility of the state Ministry of Tourism, Culture and Environment, there are clearly other departments with an indirect interest in the industry, including departments within . the Ministry of Local Government. In practice, coordination between various departments is difficult to achieve, hindering the overall planning of tourism within the state. However, because tourism is developing at such a rapid state in Malaysia, inter ministerial jurisdictions and decisions· must be considered. Regional competition will continue to grow as each nation strives to attract tourists to their respective countries. Without quality attractions within the countries concerned, Sabah induded, the success of tourism cannot be measured as the success of a destination relies not only on the quality of attractions on offer, but also safety and security on site and the quality of the environment within the area. In view of the continuing importance tourism has to the economy of Sabah, and Malaysia, the role and capadties of Local Government authorities are seen to be of critical importance as the maintenance of attractions, ultimately fall within the control and influence of the district, in which it is sited. This research has revealed an exchange of ideas on issues related to developments in the theory and practice of developing (and managing) tourism destinations which can only be realised ifand when the roles of local government offices and the capacity of its human capital goes, in line with tourism development polides, before Sabah can achieve its full potential, and be the preferred destination of choice.